ปัจจัยคัดสรรที่มีความสัมพันธ์กับภาวะซึมเศร้าในผู้สูงอายุโรคข้อเข่าเสื่อม - ภัทราภร วิริยวงค์ (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
The purpose of this descriptive research was to examine the relationships between factors related to age, gender, income, length of illness, disability, pain, stress, social support and depression in older person with knee osteoarthritis. The subjects comprised 150 out-patients with knee osteoarthritis at orthopedic clinics, Phramongkutklao Hospital, Rajavithi Hospital and Ramathibodi Hospital, which were selected by the technique of simple random sampling. The instrumentation employed in data collection included the demographic data, the Chula ADL Index, the Brief Pain Inventory Scale, the Illness-related Stress Measurement Scale, Social Support Questionnaires and the Center for Epidemiologic Studies-Depression Scale (CES-D).The instruments were tested for content validity by a panel of experts. The reliability values of the Illness-related Stress Measurement Scale and Social Support Questionnaires were .93 and .93 respectively. Data were analyzed by the basic statistics of percentage, frequency, mean, standard deviation, Spearman Rank-Order Correlation Coefficient and Eta Coefficient with the significant level set at .05. The major findings can be summarized as follows : 1. The older person with knee osteoarthritis was [Mean] = 12.91 and indicated no depression. 2. Pain was significantly correlated with depression in older person with knee osteoarthritis at a level of .05 (rs=.205). 3. Stress was found to be positively correlated with depression in older person with knee osteoarthritis to a moderate degree at the level of .05 (rs=.569). 4. Income, disability and social support were found to be negatively correlated with depression in older person with knee osteoarthritis to a low degree at the level of .05 (rs=-.208,-.215 and -.164, respectively). 5. Age, gender and length of illness were, however, not significantly correlated with depression in senior adults with knee osteoarthritis at the level of .05.